FOREIGN LANGUAGE TRAINING FOR FUTURE ENGINEERS AND TECHNICIANS IN A GLOBAL INDUSTRY - Ishonkulov Sherzod Usmonovich (XALQARO ILMIY-AMALIY ANJUMAN "TA'LIM MAYDONI TENDENSIYALARI: KOMPETENTSIYALAR, INNOVATSIYALAR VA TEXNOLOGIYALAR", 2025)
This article examines the critical role of foreign language proficiency in the professional development of future engineers and technicians operating within the increasingly interconnected global industrial landscape. It argues that in addition to strong technical skills, competence in one or more foreign languages is becoming a crucial asset for effective communication, collaboration, and career advancement in international projects and diverse work environments. This article will explore the current state of foreign language training in engineering and technical education, highlight the benefits of multilingualism for these professionals, and propose strategies for integrating effective foreign language curricula into their academic programs.